Pengaruh College Adjustment terhadap Prokrastinasi Akademik pada Mahasiswa Baru di Masa Pandemii - Marchya Devana Titania; Temi Damayanti Djamhoer (UNISBA Press, 2023)
Abstract. College Adjustment, where freshmen must be able to adjust themselves to the college environment both in terms of academic adjustment, social adjustment, personal-emotional adjustment, and institutional attachment. However, the COVID-19 pandemic learning process change to online, thus affecting the ability of new students at the Islamic University of Bandung to conduct College Adjustment. As a result, new students are prone to Academic Procrastination or procrastination in doing academic work and lectures because they cannot adapt to the academic culture of higher education. The research is aimed to looking at the description of the level of College Adjustment and Academic Procrastination on new students at the Islamic University of Bandung and the magnitude of the influence given by the College Adjustment on the level of Academic Procrastination. The method in this study is a quantitative method and the sample of this research is the first year freshmen at the Islamic University of Bandung who experience online learning which is selected based on the sampling technique, Simple Random Sampling, totaling 348 students. The measuring instrument used is the Student Adaptation to College Questionnaire (SACQ) from Baker & Siryk (1984) to measure the College Adjustment level and the Academic Procrastination Tendency Questionnaire from Ferrari (1995). Data analysis using simple linear regression using SPSS and the results of this study indicate that the College Adjustment level of new students is included in the low level and Academic Procrastination is included in the high level, and there is a negative effect of College Adjustment on Academic Procrastination of -0.984 which means a decrease of 1 score in College Adjustment will increase Academic Procrastination by 0.984 and College Adjustment can predict the level of Academic Procrastination negatively with an estimated prediction of 50.3%. Abstrak. College Adjustment, di mana mahasiswa baru harus dapat menyesuaikan dirinya dengan lingkungan perguruan tinggi baik dalam aspek penyesuaian akademik, penyesuaian sosial, penyesuaian personal-emosional, dan kelekatan dengan institusi. Perkuliahan yang mengalami perubahan menjadi daring mempengaruhi kemampuan mahasiswa baru di Universitas Islam Bandung dalam melakukan College Adjustment. Akibatnya, mahasiswa baru rentan melakukan Prokrastinasi Akademik atau menunda-nunda dalam mengerjakan pekerjaan akademik dan perkuliahan karena tidak dapat beradaptasi dengan budaya akademik perguruan tinggi. Penelitian ini ditujukan untuk melihat gambaran tingkatan College Adjustment dan Prokrastinasi Akademik pada mahasiswa baru Universitas Islam Bandung dan besaran pengaruh yang diberikan College Adjustment terhadap tingkatan Prokrastinasi Akademik. Metode dalam penelitian ini adalah metode kuantitatif dan sampel dari penelitian ini adalah mahasiswa baru tahun pertama Universitas Islam Bandung yang mengalami pembelajaran daring yang dipilih berdasarkan Simple Random Sampling yang berjumlah 348 mahasiswa. Student Adaptation to College Questionnaire (SACQ) dari Baker & Siryk (1984) digunakan untuk mengukur tingkat College Adjustment dan Kuesioner Kecenderungan Prokrastinasi Akademik dari Ferrari (1995). Analisis data menggunakan regresi linier sederhana dengan menggunakan SPSS dan hasil dari penelitian ini menunjukkan bahwa tingkat College Adjustment mahasiswa baru termasuk kedalam tingkat rendah dan Prokrastinasi Akademik termasuk kedalam tingkat tinggi, dan hasil juga menunjukkan terdapat pengaruh negatif dari College Adjustment terhadap Prokrastinasi Akademik sebesar -0,984 yang berarti penurunan 1 skor College Adjustment akan meningkatkan Prokrastinasi Akademik sebesar 0,984 dan College Adjustment dapat memprediksi tingkat Prokrastinasi Akademik secara negatif dengan estimasi prediksi sebesar 50,3%.